2020
DOI: 10.16921/chasqui.v0i144.4282
|View full text |Cite
|
Sign up to set email alerts
|

Cobertura ambiental durante a pandemia no Brasil e em Portugal: explorando crises e (des)conexões

Abstract: Esta proposta compara de que forma dois sites de notícias do Brasil e de Portugal, o G1 e o SIC Notícias, têm apresentado a cobertura ambiental durante a pandemia e se há cruzamento das pautas climática com a disseminação do coronavírus. Realizamos uma coleta a partir da combinação de palavras-chave nos dois veículos, entre março e junho de 2020, e analisamos, por meio de categorizações temáticas, quais são as crises que são evidenciadas em cada um dos países, assim como os enfoques mais recorrentes em cada um… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“… Beling, E. et al. (2020) 24 Cobertura ambiental durante a pandemia no Brasil e em Portugal: explorando crises e (des)conexões Brazil Media Explore the journalistic coverage of the Covid-19 Pandemic and the Climate Crisis to identify if there was an intertwining approach. The coverage was fragmented, and it was complicated to understand the relationship between both crises.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Beling, E. et al. (2020) 24 Cobertura ambiental durante a pandemia no Brasil e em Portugal: explorando crises e (des)conexões Brazil Media Explore the journalistic coverage of the Covid-19 Pandemic and the Climate Crisis to identify if there was an intertwining approach. The coverage was fragmented, and it was complicated to understand the relationship between both crises.…”
Section: Resultsmentioning
confidence: 99%
“…Three articles were found related to media —this included journalism and communication broadly defined. One article 24 explored the journalistic coverage of environmental issues in two news sites —one from Brazil and one from Portugal— during the beginning of the COVID-19 pandemic, to identify if there was an intertwining approach to the coverage of both crises, climate and sanitary. The study found that there was a fragmentation in the coverage which made it difficult to comprehend the connections between the two crises.…”
Section: Resultsmentioning
confidence: 99%